2003
DOI: 10.1109/tsmcb.2003.810873
|View full text |Cite
|
Sign up to set email alerts
|

Plume mapping via hidden markov methods

Abstract: This paper addresses the problem of mapping likely locations of a chemical source using an autonomous vehicle operating in a fluid flow. The paper reviews biological plume-tracing concepts, reviews previous strategies for vehicle-based plume tracing, and presents a new plume mapping approach based on hidden Markov methods (HMM). HMM provide efficient algorithms for predicting the likelihood of odor detection versus position, the likelihood of source location versus position, the most likely path taken by the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
99
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(99 citation statements)
references
References 40 publications
0
99
0
Order By: Relevance
“…This process continues until the probability distribution of the source reduces to a Dirac function. Infotaxis [6], Hidden Markov Models [7] and Kernel methods [8], are the main examples of this category. Although these techniques are very promising with a great potential in terms of research, they suffer from high computational costs and the need of accurate localization information for the sampling points.…”
Section: Introductionmentioning
confidence: 99%
“…This process continues until the probability distribution of the source reduces to a Dirac function. Infotaxis [6], Hidden Markov Models [7] and Kernel methods [8], are the main examples of this category. Although these techniques are very promising with a great potential in terms of research, they suffer from high computational costs and the need of accurate localization information for the sampling points.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation is an effective tool, particularly to test the behaviour of complex systems that are difficult or not practical to test experimentally in real environments, like the searching of odour sources in large outdoor spaces. Farrell et al (2003) for example shown the utilization of hidden Markov methods to locate an odour source in a simulated environment. Marques et al (2002a) used a Genetic Algorithm to coordinate a group of mobile robots searching for an odour source.…”
Section: Searching Odour Sources With Multiple Robotsmentioning
confidence: 99%
“…Most of the works concerning olfactory search have focused on odor plume tracking [15]- [20] and mapping [21]- [23], whereas plume finding has received little attention. Bio-inspired [16], [17], concentration gradient climbing (chemotaxis) and up-wind directed search (anemotaxis [19], [24], [25]) are the most common approaches to track odor plumes by mobile robots.…”
Section: Introductionmentioning
confidence: 99%